2013
DOI: 10.1038/onc.2013.360
|View full text |Cite
|
Sign up to set email alerts
|

The transcriptional co-activator SND1 is a novel regulator of alternative splicing in prostate cancer cells

Abstract: Splicing abnormalities have profound impact in human cancer. Several splicing factors, including SAM68, have pro-oncogenic functions, and their increased expression often correlates with human cancer development and progression. Herein, we have identified using mass spectrometry proteins that interact with endogenous SAM68 in prostate cancer (PCa) cells. Among other interesting proteins, we have characterized the interaction of SAM68 with SND1, a transcriptional co-activator that binds spliceosome components, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
79
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 76 publications
(82 citation statements)
references
References 61 publications
(104 reference statements)
1
79
0
Order By: Relevance
“…Mass spectrometry analysis of proteins interacting with splicing factor SAM68 in prostate cancer cells showed significant accumulation of both SAM68 and TSN. 31 Upregulation of these proteins exerted interdependent synergic effect on exon v5 inclusion in the CD44 mRNA, providing further evidence for TSN as a novel regulator of alternative splicing, promoting prostate cancer cell growth and survival.…”
Section: Role Of Tsn In Carcinogenesis and Cell Deathmentioning
confidence: 99%
See 2 more Smart Citations
“…Mass spectrometry analysis of proteins interacting with splicing factor SAM68 in prostate cancer cells showed significant accumulation of both SAM68 and TSN. 31 Upregulation of these proteins exerted interdependent synergic effect on exon v5 inclusion in the CD44 mRNA, providing further evidence for TSN as a novel regulator of alternative splicing, promoting prostate cancer cell growth and survival.…”
Section: Role Of Tsn In Carcinogenesis and Cell Deathmentioning
confidence: 99%
“…Recent work has connected the function of TSN in splicing regulation to oncogenesis by demonstrating interaction of TSN with a splicing factor SAM68 in prostate cancer cells. 31 The authors have revealed that TSN can promote SAM68-dependent splicing of specific exons in DC44 mRNA, an event associated with tumor progression and metastasis. However, whether this phenomenon is specific for prostate cancer or is a more general event requires additional investigations.…”
Section: Role Of Tsn In Splicingmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, TSN is cleaved by caspases and facilitates programmed cell death during development and stress responses (Sundström et al, 2009). TSN also interacts with small ribonucleoproteins and Sm proteins involved in pre-mRNA splicing Gao et al, 2012;Cappellari et al, 2014). In plants, TSN is an RNA-binding protein involved in RNA transport and localization, which is essential for stress tolerance and has been linked to the formation of stress granules and processing bodies (Wang et al, 2008;Frei dit Frey et al, 2010;Gutierrez-Beltran et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…The binding of Sam68 near alternative splice junctions in pre-mRNAs has been shown to regulate splice site selection and regulate the usage of alternative exons (1). Sam68 promotes the inclusion of CD44 variable exon 5 (v5), and interaction of Sam68 with SND1 (staphylococcal nuclease domain 1) enhances v5 inclusion (5,6). The alternative splicing of Bcl-x is regulated by Sam68 and its interaction with hnRNPA1 and FBI-1, affecting prosurvival and apoptotic pathways (7,8).…”
mentioning
confidence: 99%